2017
DOI: 10.1364/ol.42.003804
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for visible supercontinuum light generation in integrated diamond waveguides

Abstract: We numerically show the advantages of using diamond-on-insulator (DOI) waveguides to design compact supercontinuum (SC) light sources for the visible (VIS) wavelength range. We conclude that the DOI platform is more suitable than silicon nitride waveguides for tailoring the dispersion in such a way that a zero-dispersion wavelength (ZDW) is obtained in the VIS, as is required to achieve efficient VIS SC generation (SCG). After designing a DOI waveguide that features a ZDW at ∼600  nm, we exploit it to numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The next exciting stage is to reduce the footprint of the component and generate octave spanning supercontinua on an optical chip. To this aim, various platforms have been successfully investigated: Si [9][10][11], SiGe [12][13][14], SiN [15][16][17][18], diamond-on-insulator [19], chalcogenide waveguides [20] or III-V material based waveguides (InGaP [21]) and AlGaAs [22]. Each material provides specific advantages but also strong potential limitations including two photon absorption (TPA) and associated free carrier absorption, high level of losses, limiting transparency window, low refractive index, low handling power as well as high cost or complex manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The next exciting stage is to reduce the footprint of the component and generate octave spanning supercontinua on an optical chip. To this aim, various platforms have been successfully investigated: Si [9][10][11], SiGe [12][13][14], SiN [15][16][17][18], diamond-on-insulator [19], chalcogenide waveguides [20] or III-V material based waveguides (InGaP [21]) and AlGaAs [22]. Each material provides specific advantages but also strong potential limitations including two photon absorption (TPA) and associated free carrier absorption, high level of losses, limiting transparency window, low refractive index, low handling power as well as high cost or complex manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, various platforms have been successfully investigated: Si [9][10][11], SiGe [12][13][14], SiN [15][16][17][18], diamond-on-insulator [19], chalcogenide waveguides [20] or III-V material based waveguides (InGaP [21]) and AlGaAs [22]. Each material provides specific advantages but also strong potential limitations including two photon absorption (TPA) and associated free carrier absorption, high level of losses, limiting transparency window, low refractive index, low handling power as well as high cost or complex manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…8.2±3.5 × 10 −20 m 2 W −1 in the NIR range) has been experimentally explored for chip-scale frequency comb generation in the NIR spectral domain [6]. In the visible (VIS) spectral domain, a recent study has numerically demonstrated SCD waveguides as more suitable candidates than Si 3 N 4 waveguides for VIS supercontinuum generation (SCG) due to SCD's higher refractive index (2.412 at 635 nm [7]) allowing stronger light confinement and more possibilities for dispersion engineering [8]. In the UV spectral domain, studies have numerically demonstrated the promises of using SCD for wavelength conversion in the UV range by means of Kerr and Raman-resonant wave-mixing processes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We choose three target wavelengths (850, 635 and 405 nm wavelength) by taking into account their relevance to the key photonic applications mentioned above as well as the availability of cost-efficient semiconductor lasers for optical characterization. Wavelengths in the short-wave NIR around 850 nm can be potential pump wavelengths for VIS SCG [8]. The wavelength of 635 nm is also selected because it is very close to the ZPL emission wavelength (∼637 nm) of diamond NV − centers.…”
Section: Introductionmentioning
confidence: 99%